Development and Validation of Diagnostic KASP Markers for Brown Planthopper Resistance in Rice - Ishwarya Lakshmi, V. G.; Sreedhar, M.; JhansiLakshmi, V.; Gireesh, C.; Rathod, Santosha; Bohar, Rajaguru; Deshpande, Santosh; Laavanya, R.; Kiranmayee, K. N. S. Usha; Siddi, Sreedhar; Vanisri, S. (Frontiers in Genetics, 2022)
Rice (Oryza sativa L.) is an important source of nutrition for the world's burgeoning population that often faces yield loss due to the infestation by Brown Planthopper (BPH, Nilaparvata lugens (Stål). The development of rice cultivars with BPH resistance is one of the crucial precedence in rice breeding programs. Recent progress in high-throughput SNP based genotyping technology has made it possible to develop markers linked to BPH more quickly than ever before. With this view, genome-wide association study was undertaken for deriving marker-trait associations with BPH damage score and SNPs from Genotyping-by-sequencing data of 391 Multi-parent advanced generation inter-cross (MAGIC) lines. Twenty-three significant SNPs involved in stress resistance pathways were selected from General Linear Model along with 31 SNPs reported from FarmCPU model in previous studies. Of these 54 SNPs, 20 were selected in such a way to cover 13 stress related genes. Kompetitive allele specific PCR (KASP) assays were designed for the 20 selected SNPs and were subsequently utilized in validating the genotypes that identified, 6 SNPs, viz, snpOS00912, snpOS00915, snpOS00922, snpOS00923, snpOS00927 and snpOS00929 as efficient in distinguishing the genotypes into BPH resistant and susceptible clusters. Bph17 and Bph32 genes that are highly effective against the biotype 4 of BPH have been validated by gene specific SNPs with favourable alleles in M201, M272, M344, RathuHeenati and RathuHeenati accession. These identified genotypes could be useful as donors for transferring BPH resistance into popular varieties with marker-assisted selection using these diagnostic SNPs. The resistant lines and the significant SNPs unearthed from our study can be handy in developing BPH resistant varieties after validating them in biparental populations with the potential usefulness of SNPs as causal markers.